Earn more tomorrow: Overconfidence, income expectations and consumer indebtedness - Antonia Grohmann; Lukas Menkhoff; Christoph Merkle; Renke Schmacker (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This paper examines whether biased income expectations due to overconfidence lead to higher levels of debt-taking. We show suggestive evidence for a link between overconfidence and borrowing behavior in a representative survey of German households (GSOEP-IS). This motivates a laboratory experiment to study causality behind these effects. In two experiments, participants can purchase goods by borrowing against their future income. We exogenously manipulate overconfidence about income expectations by letting income depend on relative performance in hard and easy quiz tasks. In the main experiment, we successfully generate biased income expectations and show that participants with higher income expectations initially borrow more. Overconfident participants scale back their consumption after income feedback. However, they remain in higher debt at the end of the experiment, which has real financial consequences. In a robustness experiment, we rule out that over-borrowing is driven by low prices of goods. Even though the expected income manipulation works less well in this experiment, debt-taking behavior is very similar and correlates with income expectations and overconfidence.
Keywords: D14; D84; G40; 330; Debt; Consumption; Borrowing; Overconfidence; Income Expectations